Efektifitas Teknik Relaksasi Otot Progresif untuk Mengurangi Nyeri Kepala pada Pasien Hipertensi Diruang Rawat Inap RSUI Harapan Anda Kota Tegal - Savira Chaerunisa; Tutik Rahayu; Apriliani Yulianti Wuriningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
This study aims to determine the effectiveness of progressive muscle relaxation techniques in reducing headache pain in hypertensive patients in the inpatient ward of Harapan Anda Hospital in Tegal City. Hypertension is often accompanied by complaints of headaches, which is a significant problem for patients. One non-pharmacological approach that can be used to alleviate headaches caused by hypertension is progressive muscle relaxation therapy. In this study, 55 respondents with hypertension and complaints of headache were involved. The research used a quasi-experimental design with a quantitative approach. Before and after the intervention, patients underwent progressive muscle relaxation therapy for three consecutive days, with a duration of fifteen minutes per session. Pain levels were assessed using a pain scale before and after the intervention. Data analysis was conducted using the Wilcoxon test. The results showed that 53 patients (96%) experienced a decrease in pain levels after the therapy. The average pain scale significantly decreased, with moderate pain levels reducing from 89.1% to 3.6%, while mild pain increased from 10.9% to 85.5%. The Wilcoxon test results indicated a p-value of 0.000 (p < 0.05), indicating that progressive muscle relaxation therapy is effective in reducing headache pain in hypertensive patients. This therapy has been shown to be a simple, safe method that can be applied both independently by patients and in healthcare services. Therefore, progressive muscle relaxation can be an effective alternative in managing headaches in hypertensive patients.